In situ Out-of-Plane Cyclic Testing of Original and Strengthened Traditional Stone Masonry Walls Using Airbags - Tiago Miguel Ferreira (2016)
This article presents a field experimental campaign carried out on an existing one-story stone masonry building, aiming at characterizing the out-of-plane behavior of its walls. A bidirectional test set-up based on a self-equilibrated airbag system was developed and used on three similar masonry walls under distinct conditions: original, retrofitted, and strengthened. The results obtained and the main advantages and shortcomings found in the test set-up are discussed. Finally, some of the most popular retrofitting and/or strengthening techniques applied during the 1998 Azores reconstruction process are critically analyzed, aiming at suggesting quantifications for future interventions on existing unreinforced masonry buildings.